Redefinisi Korupsi: Sebuah Tawaran Pandangan Islam - Usamah Abdurrahman; Ria Rahmawati (Universitas Darussalam Gontor, 2018)
It is widely known that the national reform emerged on virtually two decades ago has mandated the Indonesian government to demolish the corrupt practices from their origins. In fact, the existence of corruption is generally realized no longer maximally declined in today’s socio-economic life or even involves wider scopes. As a result, people tend to be more pessimistic towards attempts to curb this extraordinary crime. Even though many reasons have been offered by several scholars due to deal with this dilemma, the problems were steadily occur. Therefore, this article requiring further improvement tries to identify the fundamental issue which is rarely discussed; defnition of corruption. Through qualitative research using inductive method, a number of results have been found. Firstly, the recent defnition of corruption developed by mostly western scientists is quite inappropriate and leads to confusion instead of what have been discussed by Moslem scholars since classical era. Secondly, in Islamic point of view, recent corruption includes ghulûl, risywah, ghisy, and iḥtikâr which are addressed as economic crimes deserving certain consequences. And fnally, Islamic teaching provides the plenty of anti-corruption instruments ranging from organizing good governance in order to prevent every Moslem from committing corruption to imposing particular punishment upon the criminal.